Functional Land Management for managing soil functions: A case-study of the trade-off between primary productivity and carbon storage in response to the intervention of drainage systems in Ireland. (September 2015) - O'Sullivan, L.; Creamer, R.E.; Fealy, R.; Lanigan, G.; Simo, I.; Fenton, O.; Carfrae, J.; Schulte, R.P.O.
Highlights: Trade-offs between 'primary productivity' and 'carbon cycling' are examined. Prioritisation of these soil functions diverges between stakeholders. Agronomic benefits exceed the monetised environmental costs at current CO2 price. Large geographic variation exists in the environmental cost: agronomic benefit ratio. Functional Land Management can support more effective, tailored policies. Abstract: Globally, there is growing demand for increased agricultural outputs. At the same time, the agricultural industry is expected to meet increasingly stringent environmental targets. Thus, there is an urgent pressure on the soil resource to deliver multiple functions simultaneously. The Functional Land Management framework (Schulte et al., 2014 ) is a conceptual tool designed to support policy making to manage soil functions to meet these multiple demands. This paper provides a first example of a practical application of the Functional Land Management concept relevant to policy stakeholders. In this study we examine the trade-offs, between the soil functions 'primary productivity' and 'carbon cycling and storage', in response to the intervention of land drainage systems applied to 'imperfectly' and 'poorly' draining managed grasslands in Ireland. These trade-offs are explored as a function of the nominal price of 'Certified Emission Reductions' or 'carbon credits'. Also, these trade-offs are characterised spatially using ArcGIS to account for spatial variability in the supply of soil functions. To manage soil functions, it is essential to understand how individual soil functions are prioritised by those that are responsible for the supply of soil functions – generally farmers and foresters, and those who frame demand for soil functions – policy makers. Here, in relation to these two soil functions, a gap exists in relation to this prioritisation between these two stakeholder groups. Currently, the prioritisation and incentivisation of these competing soil functions is primarily a function of CO2 price. At current CO2 prices, the agronomic benefits outweigh the monetised environmental costs. The value of CO2 loss would only exceed productivity gains at either higher CO2 prices or at a reduced discount period rate. Finally, this study shows large geographic variation in the environmental cost: agronomic benefit ratio. Therein, the Functional Land Management framework can support the development of policies that are more tailored to contrasting biophysical environments and are therefore more effective than 'blanket approaches' allowing more specific and effective prioritisation of contrasting soil functions.